Przedstaw w postaci iloczynu :
3by-6b=
xy-x(do potęgi2)y=
12ab(do potęgi2)+16b(do potęgi2)=
2xy+3x-x(do potęgi2)-y=
-8xy+8x=
x(do potęgi3)-2x(do potęgi2)+x=
Wyłącz przed nawias jednomian 2x
2x-2xy=
6x(do potęgi2)-12x=


SZYBKO PROSZĘ ! ! !

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T12:16:18+01:00
3by-6b=3*b*y-2*3*b=3b(y-2)
xy-x²y=x*y-x*x*y=xy(1-x)
12ab²+16b²=3*4*a*b²+4*4*b²=4b²(3a+4)
2xy+3x-x²-y=3x-x*x-y+2*x*y=x(3-x)-y(1+2x)
-8xy+8x=8x(-y+1)
x³-2x²+x=x(x²-2x+1)

2x-2xy=2x(1-y)

6x²-12x=6*x*x-2*6*x=6x(x-2)
6x²-12x=2*3*x*x-2*6*x=2x(3x-6)
6 2 6
2010-02-28T12:31:53+01:00
3by-6b= 3b(y-2)
xy-x²y= x(y-xy)
12ab²+16b²=4b(3ab+4b)
2xy+3x-x² -y=[nie mam pomysłu]
-8xy+8x=8x(-y+1)
x³-2x²+x=
2x-2xy=2x(1-y)
6x²-12x=2x(3x-6)
2 5 2